Measurement and the Study of Motivation and Strategy Use: Determining If and When Self-report Measures are Appropriate - Peggy Van Meter (EARLI, 2020)
The goal of this special issue is to examine the use of self-report measures in the study of motivation and strategy use. This commentary reviews the articles contained in this special issue to address the primary objective of determining if and when self-report measures contribute to understanding these major constructs involved in self-regulated learning. Guided by three central questions, this review highlights some of the major, emergent themes regarding the use of self-report. The issues addressed include attention to evidence for construct validity, the need to consider broad methodological factors in the collection and interpretation of self-report data, and the innovations made possible by modern tools for administering and analyzing self-report measures. Conclusions forward a set of conditions for the use of self-report measures, which center on the role of theoretically-driven choices in both the selection of self-report measures and analysis of the data these measures generate.